2013
DOI: 10.1021/la303931c
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering Dye-Labeled Au Nanoparticles for Triplexed Detection of Leukemia and Lymphoma Cells and SERS Flow Cytometry

Abstract: The labeling of cell surface receptors by fluorescent markers is an established method for the identification of cell phenotype in both research and clinical settings. Fluorescence dye labeling has inherent constraints, most notably the upper limit of labels per cell that may be probed using a single excitation source, in addition to a physical limit to the number of broad emission spectra that can be distinctly collected within the visible wavelength region. SERS labeling has the potential to mitigate these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 51 publications
0
65
0
1
Order By: Relevance
“…332 Later, MacLaughlin et al reported the use of SERS flow cytometry in identifying leukemia and lymphoma cells. 333 Here, 60 nm gold core SERS tags were conjugated to antibodies and used to detect three B cell surface markers (CD45, CD19, and CD20). Cell labeling was performed on two cell lines derived from patient samples, chronic lymphocytotic leukemia and LY10 cells.…”
Section: Cellular Labeling and Profilingmentioning
confidence: 99%
“…332 Later, MacLaughlin et al reported the use of SERS flow cytometry in identifying leukemia and lymphoma cells. 333 Here, 60 nm gold core SERS tags were conjugated to antibodies and used to detect three B cell surface markers (CD45, CD19, and CD20). Cell labeling was performed on two cell lines derived from patient samples, chronic lymphocytotic leukemia and LY10 cells.…”
Section: Cellular Labeling and Profilingmentioning
confidence: 99%
“…3). Whilst only one cell type was detected in this study, three separate surface biomarkers could be simultaneously distinguished using Raman tags covalently bound to Au NPs [30]. An additional novelty in this study was the use of flow cytometry to differentiate between the different biomarkers.…”
Section: Figurementioning
confidence: 96%
“…SERS spectra of the three tags are shown in the corresponding spectra to the right. Flow cytometry can also be used to detect Raman tags (bottom graph), in this case malachite green (MGblack line), as shown by the shift in SERS intensity compared to Raman negative control (gray area)[30]. Copyright American Chemical Society, 2013.…”
mentioning
confidence: 99%
“…During the disease process, there are certain complex changes that occur in cells ranging from the molecular integrity to cell morphology [5]. There are various schemes used to detect diseases, including the use of dye marker labelling, enzyme-base labelling assays and nucleic acid-based assays [6,7,8,9,10]. All of these methods form the basis for nearly all of the pathology laboratory tests in hospitals.…”
Section: Introductionmentioning
confidence: 99%